Developing an e-module to improve the seventh-grade student's bump pass skills in volleyball - Yoda, I Ketut; Kasih, Indra; Ilra, Taqi (Journal of Education and e-Learning Research, 2024)
The objective of this study is to develop e-modules for bump pass learning for seventh-grade students. This study identified the problems and needs of students in learning bump pass skills, e-module eligibility and the effect of the e-module on students' bump pass skills. Two groups of seventh grades, two teachers serving as content experts and two media experts participated in this study at State Junior High School 1 Talawi. Five steps were used in conducting this research: analysis, design, development, implementation and evaluation. The researchers collected data through questionnaires, interviews, observation, documentation, expert testing and tests. The questionnaire, interview, observation and documentation results were analyzed using an interactive data analysis model. Expert test data were analyzed using the inter-rater agreement model and test result data were analyzed using an independent t-test. There are three findings in this research. First, the reason for the students' difficulties in learning bump passes is their lack of interest in the content found in their textbooks. They need learning media that are interesting and can be accessed through smartphones. Thus, e-modules are a suitable learning medium to solve problems and meet their needs. Second, the developed e-module was confirmed to have high content validity and meet the criteria for good learning materials and media based on the feasibility test results. Third, the e-module has positively and significantly affected students' understanding and bump pass skills. Thus, it is suggested that the module be used for teaching bump pass skills at other schools.